Enhanced detection of ATTR amyloid using a nanofibril-based assay. (3rd July 2021) - Rahman, M. Mahafuzur; Schmuck, Benjamin; Hansson, Henrik; Härd, Torleif; Westermark, Gunilla T.; Sandgren, Mats
Abstract: More than 30 proteins and peptides have been found to form amyloid fibrils in human diseases. Fibrils formed by transthyretin (TTR) are associated with ATTR amyloidosis, affecting many vital organs, including the heart and peripheral nervous system. Congo red staining is the gold standard method for detection of amyloid deposits in tissue. However, Congo red staining and amyloid typing methods such as immunofluorescence labelling are limited to relatively large deposits. Detection of small ATTR deposits present at an early stage of the disease could enable timely treatment and prevent severe tissue damage. In this study, we developed an enhanced ATTR amyloid detection method that uses functionalised protein nanofibrils. Using this method, we achieved sensitive detection of monomeric TTR in a microplate immunoassay and immunofluorescence labelling of ex vivo tissue from two patients containing ATTR aggregates. The system's utility was confirmed on sections from a patient with AA amyloidosis and liver sections from inflamed mouse. These results suggest that the detection system constitutes important new technology for highly sensitive detection of microscopic amounts of ATTR amyloid deposited in tissue.